2013
DOI: 10.4018/ijavet.2013100105
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Improvisation of Instructional Materials for Nigerian Home Economics Curriculum Delivery

Abstract: A structured questionnaire, designed on a 5-point scale, was used to collect data. Findings indicated that some of the challenges faced by the teachers include how to: improvise materials to arouse and sustain learners' optimism and enthusiasm; access expert assistance and technical support; stay informed of innovative developments; have confidence to share ideas with other teachers; interpret research and statistical data; diplomatically handle students' resistance; align improvised materials with curriculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…It is not surprising therefore that pupils never learn or retain what occurs in the course of these projects. In line with this study, Olibie et al (2013) observed that teachers find a sense of achievement in keeping pupils busy with projects, with little questioning as to whether the experience provided have led to increased language learning.…”
Section: Discussion and Implication Of Findingssupporting
confidence: 75%
See 2 more Smart Citations
“…It is not surprising therefore that pupils never learn or retain what occurs in the course of these projects. In line with this study, Olibie et al (2013) observed that teachers find a sense of achievement in keeping pupils busy with projects, with little questioning as to whether the experience provided have led to increased language learning.…”
Section: Discussion and Implication Of Findingssupporting
confidence: 75%
“…Researchers have sought to document and understand differences in the ways teachers draw from materials to design instruction (Brown, 2009;Collopy, 2003;Lloyd, Remillard & Herbel-Eisenmann, 2009;Olibie, Nwabunwanne & Ezenwanne, 2013;Sherin & Drake, 2009). The integration of such instructional materials in classroom practice is believed to bolster the quality of instruction by fostering student-centered pedagogies (Abdo & Semela 2010;Burman & Mutendwahothe, 201;Davis & Krajcik, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, inaccessibility of TLMs in Nigeria has been attributed mainly to unavailability in their required formats or content, coupled with the absence of a vibrant local industry for the production of the required materials and high cost of importing them (Federal Ministry of Education, 2015, p. 42;Moja, 2000). Lack of expert assistance and technical support, and inability to keep abreast with current innovative developments, are some of the factors that have been identified as hindrances to the ability of teachers to improvise instructional materials, with matters of copyright not highlighted (Olibie et al, 2013). The Nigerian copyright system is largely ineffective in controlling infringement of protected works (Oguamanam, 2011;Solanke, 2014).…”
Section: Introductionmentioning
confidence: 99%